Graphite-phase carbon nitride material with N defects as well as preparation method and application of graphite-phase carbon nitride material
By preparing graphite phase carbon nitride materials with N defects, the inefficiency problem of existing carbon nitride-based photocatalytic materials in photocatalytic water decomposition and hydrogen production is solved, and the efficient visible photocatalytic hydrogen production effect is achieved.
Patent Information
- Application Number
- CN202311216441.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing carbon nitride-based photocatalytic materials show low efficiency in photocatalytic water decomposition and hydrogen production, mainly due to their low crystallinity, small specific surface area, poor electrical transmission, wide band gap width and high electron-hole recombination rate.
Using melamine as the raw material, graphite phase carbon nitride material with N defects is prepared by hydrothermal treatment and thermal polymerization. This material has a two-dimensional porous structure, a large specific surface area and excellent visible photocatalytic properties.
The efficiency of photocatalytic water decomposition and hydrogen production is significantly improved, and it has excellent visible photocatalytic hydrogen production activity, and it also shows good hydrogen production effects in a fully water-removing system without adding sacrificial agent.
Smart Images

Figure CN119657189A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysts, and in particular to a graphite phase carbon nitride material with N defects and a preparation method and application thereof.
[0002] Background
[0003] Rapid industrialization and population growth have brought significant environmental pollution and energy technology challenges. It is estimated that global energy consumption will increase by 860 trillion kJ by 2040. The increasing consumption of non-renewable energy such as natural gas, coal, nuclear energy, and oil has not only caused an imbalance in the ecological environment, but also led to a series of environmental pollution problems. Hydrogen energy, as a high-quality and highly potential "energy carrier", has the highest calorific value of all fuels and does not produce any toxic by-products. The resulting photocatalytic water decomposition hydrogen production technology represents a sustainable and pollution-free technology that is more suitable for meeting future energy challenges.
[0004] Since 1972, Fujishima and Honda have been in TiO 2 Since the discovery of water photolysis on electrodes, a large number of materials have been found to have photocatalytic properties, mainly including metal-based photocatalytic materials and non-metal-based photocatalytic materials. In recent years, carbon nitride-based photocatalytic materials have been widely used in the research of photocatalysts because of their low cost and good light response ability. Among them, graphite carbon nitride (gC 3 N 4 ) is a typical carbon nitride-based photocatalytic material with a bandgap of about 2.7 eV. However, the original carbon nitride synthesized by the thermally induced polycondensation reaction of traditional nitrogen-containing precursors usually exhibits low crystallinity and small specific surface area, and also has problems such as poor electrical transport, wide bandgap, high electron-hole recombination rate and low quantum efficiency, making it difficult to achieve efficient photocatalytic water decomposition and hydrogen production performance, thereby limiting the widespread application of carbon nitride-based photocatalytic materials in the field of photocatalysis. At the same time, the existing tubular carbon nitride also has the disadvantages of uneven structure, weak structure, small specific surface area, weak light absorption ability, easy recombination of photogenerated electrons and holes, and poor photocatalytic performance. The existence of these disadvantages greatly limits the widespread application of tubular carbon nitride as a carrier material in the construction of heterojunction composite materials, and it is difficult to meet the needs of the photocatalytic field. However, since most semiconductors used as photocatalysts can only be activated by ultraviolet light and part of visible light, and photogenerated electrons and holes have a high recombination rate. Therefore, for gC 3 N 4 The modification and optimization of photocatalytic hydrogen production have important guiding significance for the future research direction. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, and to provide a graphite phase carbon nitride material with N defects and a preparation method and application thereof. The catalyst is a non-metallic polymer graphite phase carbon nitride containing N vacancies. The preparation method is simple, the materials are single, and the preparation cost of the catalyst is greatly reduced. The obtained graphite phase carbon nitride material with N defects has excellent visible light catalytic hydrogen production activity, has excellent hydrogen production effect in a photocatalytic semi-water splitting system, and also has a good hydrogen production effect in a full water splitting system without adding a sacrificial agent, and has good social benefits.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0007] The invention provides a graphite phase carbon nitride material with N defects. The microscopic morphology of the carbon nitride material is a two-dimensional porous structure. The N defects include N vacancies and cyano groups.
[0008] Preferably, the specific surface area of the graphite phase carbon nitride material with N defects is 95.93 m 2 / g, pore volume 0.35cm 3 / g.
[0009] The present invention provides a method for preparing a graphite phase carbon nitride material having N defects, comprising the following steps:
[0010] (1) using melamine as a raw material, adding deionized water and nitric acid for hydrothermal treatment to obtain a precursor;
[0011] (2) The precursor is subjected to thermal polymerization treatment to obtain the carbon nitride material.
[0012] Furthermore, in step (1), the ratio of the melamine to the nitric acid is 2 g:1.3 mL to 2 mL.
[0013] Furthermore, the step (1) is specifically as follows:
[0014] S1, adding melamine to deionized water, ultrasonically dispersing, and then adding nitric acid to obtain a first reaction solution;
[0015] S2, placing the first reaction solution in a high-temperature water bath, adding deionized water, stirring and dissolving in a water bath to obtain a second reaction solution;
[0016] S3, transfer the second reaction liquid into a reaction kettle and hydroheat at 180°C for 10 hours;
[0017] S4. After the reaction kettle is cooled, the white precipitate is taken out, and the precursor is obtained after centrifugal washing and drying.
[0018] Preferably, in step S1, the ratio of melamine to deionized water is 2 g:100 mL; in step S2, the water bath temperature is 90° C., and the water bath reaction time is 60 min.
[0019] Preferably, in step S1, the power of the ultrasonic dispersion treatment is 100 W, and the ultrasonic treatment time is 3 min.
[0020] Preferably, in step S4, the drying temperature is 60°C.
[0021] Furthermore, the step (2) is specifically as follows:
[0022] SS1, take the precursor and place it in a ceramic crucible, and then put it into a muffle furnace;
[0023] SS2. Using a muffle furnace to carry out a thermal polymerization reaction according to the thermal polymerization heating program, and naturally cooling to room temperature after the thermal polymerization reaction is completed, thereby obtaining the carbon nitride material.
[0024] Preferably, in step (2), the thermal polymerization temperature program of the precursor is: heating at 5°C / min to a final temperature of 550°C, and keeping at 550°C for 3h.
[0025] As a general technical concept, the present invention also provides an application of the above-mentioned graphite-phase carbon nitride material with N defects in photocatalytic full water splitting to produce hydrogen and photocatalytic semi-water splitting to produce hydrogen.
[0026] The above application is further improved, when the graphite phase carbon nitride material with N defects is used for photocatalytic water splitting to produce hydrogen, the method comprises the following steps: ultrasonically dispersing the graphite phase carbon nitride material with N defects in deionized water from which dissolved oxygen has been removed, adding a co-catalyst and then ultrasonically mixing the mixture uniformly, and after evacuating the mixture, starting a photocatalytic water splitting hydrogen production reaction under visible light irradiation to obtain H 2 .
[0027] The above application is further improved, when the graphite phase carbon nitride material with N defects is used for photocatalytic water splitting to produce hydrogen, the deionized water used to remove dissolved oxygen is obtained by continuously introducing pure nitrogen, and the pure nitrogen treatment time is 30 minutes; the ultrasonic treatment power of the two-dimensional ultra-thin porous graphite phase nitrogen with N defects dispersed in deionized water is 100W, and the ultrasonic treatment time is 30 minutes; the ratio of the two-dimensional ultra-thin porous graphite phase nitrogen with N defects to deionized water is 0.01g:100mL; the two-dimensional ultra-thin porous graphite phase nitrogen with N defects and the co-catalyst 2% H 2 PtCl 6 6H 2The ratio of O solution is 0.01g:0.5mL; the light source used in the photocatalytic reaction is a xenon lamp with a light power of 400W; the photocatalytic reaction is carried out under stirring conditions with a rotation speed of 200rpm to 300rpm; the temperature of the photocatalytic reaction is 5°C to 7°C; and the time of the photocatalytic reaction is 0min to 300min.
[0028] When the graphite phase carbon nitride material with N defects is subjected to a photocatalytic semi-splitting water hydrogen production reaction under the condition of containing a sacrificial agent, the method comprises the following steps: dispersing the graphite phase carbon nitride with N defects in deionized water containing triethanolamine and from which dissolved oxygen has been removed, adding a co-catalyst and then ultrasonically mixing the mixture uniformly, and after vacuuming, starting a photocatalytic water splitting hydrogen production reaction under visible light irradiation to obtain H 2 .
[0029] When the graphite phase carbon nitride material with N defects is used for photocatalytic semi-splitting of water to produce hydrogen, the ratio of the two-dimensional ultra-thin porous graphite phase nitrogen with N defects to deionized water is 0.01 g:100 mL; the ratio of the two-dimensional ultra-thin porous graphite phase nitrogen with N defects to triethanolamine (sacrificial agent) is 0.01 g:0.5 mL; the two-dimensional ultra-thin porous graphite phase nitrogen with N defects to the co-catalyst 2% H 2 PtCl 6 6H 2 The ratio of O solution is 0.01g:0.5mL; the light source used in the photocatalytic reaction is a xenon lamp with a light power of 400W; the photocatalytic reaction is carried out under stirring conditions with a rotation speed of 200rpm to 300rpm; the temperature of the photocatalytic reaction is 5°C to 7°C; and the time of the photocatalytic reaction is 0min to 300min.
[0030] The technical solution provided by the present invention has the following beneficial effects:
[0031] (1) The graphite-phase carbon nitride material with N defects of the present invention has N defects in its structure including N vacancies and cyano groups, which are beneficial to adjusting the energy band structure of the catalyst and improving its light absorption capacity; the ultra-thin porous sheet structure is beneficial to providing more catalytic active sites and promoting the separation and migration of photogenerated carriers, thereby improving its catalytic performance;
[0032] (2) Using melamine as raw material, the modified catalyst is prepared by a hydrothermal reaction with nitric acid combined with a thermal polymerization process. The material cost is low, the preparation method is simple, and the environmental pollution is small, which is conducive to promotion to large-scale production;
[0033] (3) The prepared catalyst and pure gC 3 N 4 Compared with the original material, it has significantly enhanced photocatalytic performance and also has good hydrogen production effect in the photocatalytic water splitting experiment without adding sacrificial agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0035] Figure 1 The graphite phase carbon nitride material (GH 1.7 -NvCN) and the X-ray diffraction pattern of the original graphite phase carbon nitride prepared in Comparative Example 1.
[0036] Figure 2 The graphite phase carbon nitride material (GH 1.7 -NvCN) and the Fourier transform infrared spectrum (FTIR) of the original graphite phase carbon nitride prepared in Comparative Example 1.
[0037] Figure 3 The graphite phase carbon nitride material (GH 1.7 -NvCN) and the electron paramagnetic resonance spectrum (EPR) of the original graphite phase carbon nitride prepared in Comparative Example 1
[0038] Figure 4 The graphite phase carbon nitride material (GH 1.7 -NvCN) (left) and SEM images of the original graphite phase carbon nitride prepared in Comparative Example 1 (right).
[0039] Figure 5 The graphite phase carbon nitride material (GH 1.7 -NvCN) and the BET test results of the original graphite phase carbon nitride prepared in Comparative Example 1.
[0040] Figure 6 The graphite phase carbon nitride material (GH 1.7 -NvCN) and the UV-visible diffuse reflectance spectra of the original carbon nitride prepared in Comparative Example 1.
[0041] Figure 7 The graph is a rate diagram of hydrogen generation in the photocatalytic complete water splitting experiment of all graphite phase carbon nitride materials with N defects prepared in Example 1 of the present invention and the original carbon nitride prepared in Comparative Example 1.
[0042] Figure 8 The graphite phase carbon nitride material (GH 1.7-NvCN) and the rate diagram of hydrogen generation in the photocatalytic semi-splitting water experiment with the original carbon nitride prepared in Comparative Example 1. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0044] The raw materials and instruments used in the following examples are all commercially available. In the examples of the present invention, unless otherwise specified, the processes used are conventional processes and the equipment used are conventional equipment.
[0045] In order to more clearly describe the technical content of the present invention, further description is given below in conjunction with specific embodiments.
[0046] Example 1
[0047] A method for preparing the graphite phase carbon nitride material with N defects in the above embodiment comprises the following steps:
[0048] (1) Add 2 g of melamine to 100 mL of deionized water, disperse it ultrasonically for 3 min, and then add 1.7 mL of nitric acid.
[0049] (2) The reaction solution obtained in step (1) was placed in a 90°C water bath, 50 mL of deionized water was added, and stirring was continued for 60 min.
[0050] (3) The mixed solution after the water bath reaction in step (2) was transferred into a tetrafluoroethylene high-pressure reactor, and subjected to hydrothermal reaction at 180° C. for 10 hours, and then naturally cooled to room temperature.
[0051] (4) The solid product obtained after the hydrothermal treatment in step (3) is centrifuged, washed, and dried to obtain a precursor.
[0052] (5) 1.0 g of the precursor was placed in a crucible, placed in a muffle furnace, and heated at 5°C / min to a final temperature of 550°C in an air atmosphere. The final temperature was kept at 550°C for three hours and then naturally cooled to room temperature. Graphite phase carbon nitride with N defects was obtained, named GH 1.7 -NvCN.
[0053] In this example, graphite phase carbon nitride with N defects was prepared with nitric acid addition amounts of 1.3 mL, 1.5 mL, and 2 mL, respectively, and was named GH 1.3 -NvCN, GH 1.5 -NvCN, GH 2 -NvCN.
[0054] Comparative Example 1
[0055] A method for preparing original graphite phase carbon nitride comprises the following steps:
[0056] According to the traditional method, melamine is thermally polymerized in an air atmosphere to prepare graphite phase carbon nitride. The specific method is: 5g of melamine is placed in a covered crucible and heated to a final temperature of 550°C at 5°C / min, and then naturally cooled to room temperature after being kept at the final temperature of 550°C for three hours. The block sample obtained after calcination is ground to obtain a yellow powder, which is the original graphite phase carbon nitride.
[0057] Figure 1 The graphite phase carbon nitride (GH) with N defects prepared in Example 1 of the present invention 1.7 -NvCN) and the X-ray diffraction pattern of the original graphite phase carbon nitride prepared in Comparative Example 1. Figure 1 It can be seen that the two characteristic diffraction peaks of graphite phase carbon nitride with N defects are significantly weaker than those of original carbon nitride, indicating the destruction of the long-range in-plane structural order within the framework and the destruction of the periodic interlayer structure. It is worth noting that the (0 0 2) diffraction peak of graphite phase carbon nitride with N defects moves from 27.4° to 27.6°, indicating that the inter-substrate distance of graphite phase carbon nitride with N defects changes from 0.33nm to 0.32nm, which may accelerate interlayer electron transfer and facilitate the migration and separation of photogenerated carriers.
[0058] Figure 2 The graphite phase carbon nitride (GHN) with N defects prepared in Example 1 of the present invention is shown. 1.7 -NvCN) and the original graphite phase carbon nitride prepared in Comparative Example 1. Figure 2 It can be seen that graphite carbon nitride (GH 1.7 -NvCN) and the original graphite phase carbon nitride have the same basic characteristic peaks. Among them, 810cm -1 The peak at 1200-1700 cm-1 belongs to the out-of-plane bending mode of the heptazine ring. -1 The sharp peaks between 3000 and 3400 cm are related to the stretching vibrations of the aromatic CN heterocycles, demonstrating the generation of an extended network of CNC bonds. -1 The broad absorption band in the range originates from H 2 The stretching vibration mode of O molecules and terminal amino groups (-NHx) absorption. However, for graphite carbon nitride with N defects, some changes will occur after nitric acid modification. First, 810cm -1 The peak at 2010cm -1A new peak appears at 3000-3400cm, which is attributed to the asymmetric stretching vibration of cyano group (-C≡N). The formation of cyano group means the destruction of periodic stacking structure, and also forms N defects, which leads to the fluctuation of graphite carbon nitride structure layer. In addition, graphite carbon nitride with N defects has a peak at 3000-3400cm -1 The NH stretching vibration intensity is significantly reduced, but the -C≡N stretching vibration is still maintained. The above characterization results show that nitric acid modification can reduce the concentration of NH groups and introduce -C≡N groups, resulting in N defects.
[0059] Figure 3 The graphite phase carbon nitride (GHN) with N defects prepared in Example 1 of the present invention is shown. 1.7 -NvCN) and the EPR graph of the original graphite phase carbon nitride prepared in Comparative Example 1. As shown in the figure, the original graphite phase carbon nitride and the graphite phase carbon nitride with N defects present the same paramagnetic absorption signal, and the g value is 2.0067. This is due to the sp in the p conjugated aromatic ring. 2 -C produces the same type of unpaired electrons. More importantly, after the introduction of -C≡N and N vacancies, the Lorentz line of graphitic carbon nitride with N defects is stronger than that of the original graphitic carbon nitride, which is mainly due to the strong electron-withdrawing properties of the -C≡N group and the N vacancy, which leads to the delocalization and concentration of isolated valence electrons in the p-conjugated heterocycle. Specifically, the loss of N atoms in the structure leaves extra electrons, which are redistributed to adjacent C atoms to form additional unpaired electrons. The above results show that the introduction of double defect sites optimizes the electronic structure of graphitic carbon nitride with N defects, and this electron-rich structure can provide more electrons to participate in the photocatalytic reduction reaction.
[0060] Figure 4 The graphite phase carbon nitride (GHN) with N defects prepared in Example 1 of the present invention is shown. 1.7 -NvCN) and the SEM image of the original graphite phase carbon nitride prepared in Example 1. It can be seen from the figure that the microstructure of the original graphite phase carbon nitride is a block structure without obvious pores. In contrast, the graphite phase carbon nitride with N defects (GH 1.7 -NvCN) microstructure showed a fluctuating layer structure, and ammonia etching caused a large number of pores. Figure 5 The graphite phase carbon nitride material (GH 1.7 -NvCN) and the original graphite phase carbon nitride prepared in Comparative Example 1. The results show that the graphite phase carbon nitride with N defects (GH 1.7 -NvCN) has a larger specific surface area and more pores than the original graphite phase carbon nitride. 2The adsorption / desorption isotherms belong to type IV and are accompanied by H3 hysteresis loop characteristics, indicating that it has a mesoporous structure. 1.7 -NvCN) with a specific surface area and pore volume of 95.93 m 2 / g and 0.35cm 3 / g, which are 11.47 and 8.75 times that of BCN, respectively. In addition, graphite carbon nitride with N defects has a wide pore size distribution. Therefore, at high relative pressure (P / P0), graphite carbon nitride with N defects exhibits stronger N 2 The above structural properties are consistent with the photocatalytic surface morphology after the introduction of -C≡N groups and N vacancies. For the visible light-driven water splitting process, porous structures and larger surface areas are preferred, which can provide more exposed active sites and abundant boundaries, thereby further improving the contact with the reactant molecules, thereby facilitating the transfer of photogenerated carriers.
[0061] Figure 6 The graphite phase carbon nitride (GH) with N defects prepared in Example 1 of the present invention 1.7 -NvCN) and the original graphite phase carbon nitride prepared in Comparative Example 1, showing that the modified catalyst has stronger absorption capacity and significant red shift for ultraviolet and visible light.
[0062] Example 2
[0063] Application of a graphite-phase carbon nitride material with N defects in visible light photocatalytic complete water splitting to produce hydrogen.
[0064] Take 10 mg of the graphite phase carbon nitride (GH 1.7 -NvCN, GH 1.3 -NvCN, GH 1.5 -NvCN, GH 2 -NvCN) and 100 mg of the original graphite phase carbon nitride prepared in Comparative Example 1 were dispersed in 100 mL of deionized water from which dissolved oxygen had been removed and 2% chloroplatinic acid hexahydrate (H 2 PtCl 6 6H 2 O) solution to provide a catalyst promoter, ultrasonic treatment for 30 minutes and then photodeposition for 1 hour. After the system is evacuated, the xenon light source is turned on to perform photoreaction. Every 1 hour, the amount of hydrogen produced is online detected and analyzed by gas chromatograph. The reaction is carried out for a total of 5 hours.
[0065] The graphite phase carbon nitride (GH) with N defects prepared in Example 1 of the present invention 1.7 -NvCN, GH 1.3 -NvCN, GH 1.5-NvCN, GH 2 The hydrogen generation in the photocatalytic water splitting experiment of the original graphite phase carbon nitride prepared in Example 1 is shown in FIG. Figure 7 As shown in the experimental results, the best hydrogen production rates of the tested photocatalysts are as follows from high to low: GH 1.7 -NvCN>GH 1.5 -NvCN>GH 2 -NvCN>GH 1.3 -NvCN>original graphite phase carbon nitride. Among them, GH 1.7 -NvCN has the best hydrogen production performance, and its optimal hydrogen production rate can reach 2.78mmol·g -1 ·h -1 The average hydrogen production rate within five hours is 1.13mmol·g -1 ·h -1 ; The optimal hydrogen production rate of the original carbon nitride is 0.12mmol·g -1 ·h -1 The average hydrogen production rate within five hours is 0.05mmol·g -1 ·h -1 .
[0066] Example 3
[0067] Application of a graphite-phase carbon nitride material with N defects in visible light photocatalytic semi-splitting of water to produce hydrogen.
[0068] Take 10 mg of the graphite phase carbon nitride (GH 1.7 -NvCN) and 100 mg of the original graphite phase carbon nitride prepared in Comparative Example 1 were dispersed in 100 mL of deionized water from which dissolved oxygen had been removed and 2% chloroplatinic acid hexahydrate (H 2 PtCl 6 6H 2 O) solution and 500 μL triethanolamine as a co-catalyst and sacrificial agent, ultrasonic treatment for 30 minutes and then photodeposition for 1 hour. After the system is evacuated, the xenon light source is turned on to carry out photoreaction. Every 1 hour, the amount of hydrogen produced is online detected and analyzed by gas chromatograph. The reaction is carried out for a total of 5 hours.
[0069] The graphite phase carbon nitride photocatalyst (GH 1.7 The hydrogen generation in the photocatalytic semi-splitting water experiment of the original graphite phase carbon nitride prepared in Example 1 is shown in FIG. Figure 7 As shown in the experimental results, it can be seen that the optimal hydrogen production rate of the tested graphite phase carbon nitride material with N defects is higher than that of the original graphite phase carbon nitride. 1.7-NvCN has the best hydrogen production performance, and its optimal hydrogen production rate can reach 50.84mmol·g -1 ·h -1 The average hydrogen production rate within five hours is 28.09mmol·g -1 ·h -1 ; The optimal hydrogen production rate of the original carbon nitride is 0.69mmol·g -1 ·h -1 The average hydrogen production rate within five hours is 0.52mmol·g -1 ·h -1 .
[0070] Example 4
[0071] Application of a graphite-phase carbon nitride material with N defects in visible light photocatalytic semi-splitting of water to produce hydrogen.
[0072] Take 10 mg of the graphite phase carbon nitride photocatalyst (GH 1.7 -NvCN) and 100 mg of the original graphite phase carbon nitride prepared in Comparative Example 1 were dispersed in 100 mL of deionized water from which dissolved oxygen had been removed and 2% chloroplatinic acid hexahydrate (H 2 PtCl 6 6H 2 O) solution and 5 mL of triethanolamine as a co-catalyst and sacrificial agent, ultrasonic treatment for 30 min and then photodeposition for 1 h. After the system was evacuated, the xenon light source was turned on to perform photoreaction. Every 1 h, the amount of hydrogen produced was analyzed online using a gas chromatograph, and the reaction was carried out for a total of 5 h.
[0073] The graphite phase carbon nitride photocatalyst (GH 1.7 The hydrogen generation in the photocatalytic semi-splitting water experiment of the original graphite phase carbon nitride prepared in Example 1 is shown in FIG. Figure 8 As shown in the experimental results, it can be seen that the optimal hydrogen production rate of the tested graphite phase carbon nitride material with N defects is higher than that of the original graphite phase carbon nitride. 1.7 -NvCN has the best hydrogen production performance, and its optimal hydrogen production rate can reach 17.15mmol·g -1 ·h -1 The average hydrogen production rate within five hours is 15.95mmol·g -1 ·h -1 ; The optimal hydrogen production rate of the original carbon nitride is 0.46mmol·g -1 ·h -1 The average hydrogen production rate within five hours is 0.43mmol·g -1 ·h -1 .
[0074] From the above content, it can be seen that the graphite phase carbon nitride material with N defects in the present invention has the advantages of strong light absorption ability, low photogenerated electron-hole recombination rate, good photocatalytic performance, good stability, etc. It is a new type of carbon nitride photocatalytic material, which can be widely used in photocatalytic water decomposition to produce hydrogen and has a good application prospect.
[0075] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A graphite phase carbon nitride material having N defects, characterized in that: The microstructure of the carbon nitride material is a two-dimensional porous structure, and the N defects include N vacancies and cyano groups.
2. The carbon nitride material according to claim 1, characterized in that The specific surface area of the carbon nitride material is 95.93 m 2 / g, pore volume 0.35cm 3 / g.
3. A method for preparing a graphite phase carbon nitride material having N defects, comprising the following steps: (1) using melamine as a raw material, adding deionized water and nitric acid for hydrothermal treatment to obtain a precursor; (2) The precursor is subjected to thermal polymerization treatment to obtain the carbon nitride material.
4. The preparation method according to claim 3, characterized in that: In step (1), the ratio of the melamine to the nitric acid is 2 g:1.3 mL to 2 mL.
5. The preparation method according to claim 4, characterized in that: The step (1) is specifically: S1, adding melamine to deionized water, ultrasonically dispersing, and then adding nitric acid to obtain a first reaction solution; S2, placing the first reaction solution in a high-temperature water bath, adding deionized water, stirring and dissolving in a water bath to obtain a second reaction solution; S3, transfer the second reaction liquid into a reaction kettle and hydroheat at 180°C for 10 hours; S4. After the reaction kettle is cooled, the white precipitate is taken out, and the precursor is obtained after centrifugal washing and drying.
6. The preparation method according to claim 5, characterized in that: In step S1, the ratio of melamine to deionized water is 2 g:100 mL; in step S2, the water bath temperature is 90° C., and the water bath reaction time is 60 min.
7. The preparation method according to claim 5, characterized in that: In step S1, the power of the ultrasonic dispersion treatment is 100 W, and the ultrasonic treatment time is 3 min.
8. The method according to claim 3, characterized in that In step (2), the thermal polymerization temperature program of the precursor is: heating at 5°C / min to a final temperature of 550°C, and keeping at 550°C for 3h.
9. The preparation method according to claim 7, characterized in that: The step (2) is specifically: SS1, take the precursor and place it in a ceramic crucible, and then put it into a muffle furnace; SS2. Using a muffle furnace to carry out a thermal polymerization reaction according to the thermal polymerization heating program, and naturally cooling to room temperature after the thermal polymerization reaction is completed, thereby obtaining the carbon nitride material.
10. Use of the graphite-phase carbon nitride material with N defects according to any one of claims 1 to 2 or the graphite-phase carbon nitride material with N defects obtained by the preparation method according to any one of claims 3 to 8 in visible light photocatalytic full water splitting to produce hydrogen or visible light photocatalytic semi-water splitting to produce hydrogen.